Durability characteristics of high and ultra-high performance concretes - Muazzam Ghous Sohail (16932480) (2021)
Durability characteristics of high-performance concrete (HPC) and ultra-high performance concrete (UHPC) are evaluated in comparison to normal strength concrete (NSC). HPC and UHPC are cast using commonly available materials with no special heat treatment. Concrete resistivity, rapid chloride permeability, sorptivity, porosity, and resistance to chloride migration and carbonation of these three types of concrete are assessed. Microstructure and hydration products are investigated using scanning electron microscope (SEM) imaging and X-ray diffraction (XRD) analyses, respectively. Potential enhancement in the service life of reinforced concrete (RC) structures when concrete is replaced with HPC and UHPC is predicted using the time-to-corrosion model. Dense microstructures, high electrical resistance, negligible chloride permeability, low sorptivity, no carbonation ingress are observed in HPC and UHPC. The chloride diffusion coefficient was found to be at least three orders of magnitude lower in UHPC compared to NSC, which could delay the corrosion initiation of steel reinforcement. With such positive attributes, these concretes are expected to find more widespread application in concrete structures in harsh-climatic conditions. This paper provides additional data and analysis that could accelerate the adoption of these materials in practice. Other Information Published in: Journal of Building Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jobe.2020.101669